BREEDING SEASON, SEXUAL MATURITY AND FECUNDITY OF THE BLUE CRAB, Portunus pelagicus (L.) IN SELECTED COASTAL WATERS IN LEYTE AND VICINITY, PHILIPPINES - Batoy, Corazon B.; Sarmago, Josephine F.; Pilapil, Bernardita C. (Annals of Tropical Research, 1987)
Breeding activity of the blue crab Portunus pelagicus (L.) was found to be continuous all throughout the year with peak periods during the first and last quarters of the year. Fluctuations in gonad indices of males and females do not necessarily follow the same pattern because the female can store and keep viable mature spermatozoa in their spermatheca for a period of several months. This may facilitate the production of successive broods without necessitating copulation for fertilization. The reproductive cycle of males peaks slightly earlier in the breeding season than that of females. Start of sexual maturity is indicated at a carapace length slightly below 40 mm and males seem to mature earlier than females. Fecundity ranges from 420,976 to 1,312,238 with a mean of 894,284 for crabs 41-70 mm in length. No significant correlations were observed between monthly gonad index and monthly means of temperature, dissolved oxygen and water transparency. However, salinity seemed to be one of the most important ecological factors affecting the species' reproductive cycle with higher salinities being favorable for breeding.